Realist Cinema as World Cinema Non-cinema, Intermedial Passages, Total Cinema (Film Culture in Transition, 2020)
"Lúcia Nagib redefines realism not as a mere question of rhetoric or style, or a product of a certain age and place, but as a deep and steadfast commitment of filmmakers to an "ethics of the real" based on various forms of engagement with physical reality, which may include "passages" provided by the other arts. Her incisive theoretical arguments and finely nuanced close readings will change forever how we think of the unity of art and reality, or the role of intermediality in cinema". - Agnes Petho, Professor of Film Studies, Sapientia Hungarian University of Transylvania "With a rare combination of depth and range, Lúcia Nagib reframes the debate about realism in cinema by connecting it with a world cinema framework and looking at the work of directors as diverse as Abderrahmane Sissako, Edgar Reitz, Wim Wenders, Mizoguchi Kenji and Lucchino Visconti through the lens of the concept of intermediality. In this lucid and beautifully written tour de force of a book, Nagib offers fascinating new readings of classical works of cinema and extends an exciting invitation to film scholars and the broader public to think differently about possible new pathways to and through the history of film as an art form". - Vinzenz Hediger, Professor of Cinema Studies, Goethe Universität Frankfurt